Clinical Characteristics and Outcome of Drug‐Induced Liver Injury in the Older Patients: From the Young‐Old to the Oldest‐Old. Issue 4 (6th December 2020) - Weersink, Rianne A.; Alvarez‐Alvarez, Ismael; Medina‐Cáliz, Inmaculada; Sanabria‐Cabrera, Judith; Robles‐Díaz, Mercedes; Ortega‐Alonso, Aida; García‐Cortés, Miren; Bonilla, Elvira; Niu, Hao; Soriano, German; Jimenez‐Perez, Miguel; Hallal, Hacibe; et al.
Abstract : Older patients with hepatotoxicity have been scarcely studied in idiosyncratic drug‐induced liver injury (DILI) cohorts. We sought the distinctive characteristics of DILI in older patients across age groups. A total of 882 DILI patients included in the Spanish DILI Registry (33% ≥ 65 years) were categorized according to age: "young" (< 65 years); "young‐old" (65–74 years); "middle‐old" (75–84 years); and "oldest‐old" (≥ 85 years). All elderly groups had an increasingly higher comorbidity burden ( P < 0.001) and polypharmacy ( P < 0.001). There was a relationship between jaundice and hospitalization ( P < 0.001), and both were more prevalent in the older age groups, especially in the oldest‐old (88% and 69%, respectively), and the DILI episode was more severe ( P = 0.029). The proportion of females decreased across age groups from the young to the middle‐old, yet in the oldest‐old there was a distinct female predominance. Pattern of liver injury shifted towards cholestatic with increasing age among top culprit drugs amoxicillin‐clavulanate, atorvastatin, levofloxacin, ibuprofen, and ticlopidine. The best cutoff point for increased odds of cholestatic DILI was 65 years. Older patients had increased non–liver‐related mortality ( P = 0.030) as shown by the predictive capacity of the Model for End‐Stage Liver Disease score (odds ratio (OR) = 1.116; P < 0.001), and comorbidity burden (OR = 4.188; P = 0.001) in the 6‐month mortality. Older patients with DILI exhibited an increasingly predominant cholestatic phenotype across a range of culprit drugs, other than amoxicillin‐clavulanate, with increased non–liver‐related mortality and require a different approach to predict outcome. The oldest DILI patients exhibited a particular phenotype with more severe DILI episodes and need to be considered when stratifying older DILI populations.